Gingival Enlargement Management using Diode Laser 940 nm and Conventional Scalpel Technique (A Comparative Study) - Musaa, Farah E.; Awazli, Lutfi G.; Alhamdani, Faaiz (Iraqi Journal of Laser, 2019)
Diode lasers are becoming popular in periodontal surgery due to their highly absorption by pigments such as melanin and hemoglobin their weak absorption by water and hydroxyapatite makes them safe to be used around dental hard tissues. Objective: The aim of the present study was to evaluate the efficiency of diode laser in performing gingivectomy in comparison to conventional scalpel technique in patients with chronic inflammatory enlargement. Materials and methods: Thirty patients were selected for this study. All of them required surgical treatment of gingival enlargements and were randomly divided into two groups: Control group (treated by scalpel and include sixteen patients) and study group (treated with diode laser 940nm and include fourteen patients). Data collected during and after surgery were compared and statically analyzed. Results: Fifteen male and fifteen female were included in this study with age mean of 26.2. Significant differences were observed in the Gingival Index and bleeding scores in laser group compared to the scalpel group, while no significant differences were found in swelling score and plaque index, The level of significance was set at P≤ 0.05.Conclusion: Diode laser 940nm are beneficial in achieving hemostasis with the improvement of gingival health compared to the scalpel technique.